PENGARUH EXPERIENTIAL MARKETING TERHADAP REPURCHASE INTENTION DIMEDIASI OLEH CUSTOMER SATISFACTION PADA RESTORAN X SURABAYA - Marcellino, Louis; Ellitan, Lena; Muljani, Ninuk (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2021)
Currently, many businesses are growing rapidly, this is due tocreative and innovative ideas. Along with this idea, the concept of marketing also developed. Marketing activities are now starting to focuson customer satisfaction. In general, every business aims to seek profit,this goal cannot be separated from marketing activities. Marketing itself must be thought out in advance to be more targeted to customers.In 2013, the hotel and restaurant industry accounted for 14.33% of Indonesia's Gross Domestic Product (GDP). One example of a restaurantbusiness is X Restaurant in Surabaya. This study aims to analyze fivetypes of market experience on repurchase intentions, either directly orthrough customer satisfaction at X Restaurant in Surabaya. Object ofthis research is X Restaurant customers in Surabaya who are more than18 years old and have come to X Restaurant at least 3 times.Total sample in this study was 169 samples and using the Partial Least Square method. The data used is primary data obtained bydistributing questionnaires to customers of X Restaurant in Surabaya.In analyzing the data using a Structural Equation Modeling approachwith the help of SmartPLS software. The results of the study prove thatsense experience, feel experience, think experience, and related experience have a significant influence on customer satisfaction and repurchase intentions by mediating customer satisfaction; Customer satisfaction has a significant effect on repurchase intention; Action experience has no significant effect on customer satisfaction and repurchaseintention through customer satisfaction.